2021
DOI: 10.3390/w13081040
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Modification in Relation to Sea Storm Effects: Application of 3D Remote Sensing Survey in Sanremo Marina (Liguria, NW Italy)

Abstract: Integrated remote sensing techniques, such as photogrammetry from unmanned aerial vehicles (UAV), mobile laser scanners (MLS) and multibeam echosounders (MBES), are particularly effective in detecting and measuring coastal and seabed features and their modifications over time (4D analysis) induced by sea storms. In fact, these techniques allow the production of very high-resolution 3D models, with a continuum between above and below sea level. The present research is focused on the area of Portosole Marina (Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…The results of the UAS survey provided detailed information on the coastal impact of the storm and a detailed 3D reconstruction of the seawall sector heavily damaged during the event [53]. The 3D topographic data confirmed the occurrence of erosive processes along the seawall during the sea storm resulting in a generalized instability of the calcareous rock blocks at the base of the seawall.…”
Section: Discussionmentioning
confidence: 70%
“…The results of the UAS survey provided detailed information on the coastal impact of the storm and a detailed 3D reconstruction of the seawall sector heavily damaged during the event [53]. The 3D topographic data confirmed the occurrence of erosive processes along the seawall during the sea storm resulting in a generalized instability of the calcareous rock blocks at the base of the seawall.…”
Section: Discussionmentioning
confidence: 70%
“…Terracing has deeply modified the geomorphological, vegetation and dwelling landscape at a slope scale. Well-preserved examples of slope terracing are found in the San Fruttuoso catchment [155][156][157].…”
Section: Croce DI Fanamentioning
confidence: 99%
“…Main Objective Exclusion Cause Dominey-Howes et al (2000) [98] process identification CBDs produced by tsunami [99] vulnerability study No CBD dynamics data are reported Andriani and Walsh (2007) [100] process identification No CBD dynamics data are reported Scicchitano et al (2010) [101] process identification No CBD dynamics data are reported Furlani et al (2011) [102] process identification No CBD dynamics data are reported Paris et al (2011) [2] review preface No CBD dynamics data are reported Mastronuzzi and Pignatelli (2012) [103] process identification CBDs produced by tsunami Katz and Mushkin (2013) [104] process identification No CBD dynamics data are reported Mottershead et al (2015) [105] process identification CBDs produced by tsunami Shah-Hosseini et al ( 2016) [106] hazards study No CBD dynamics data are reported Amores et al (2020) [107] storm simulation No CBD dynamics data are reported Ruban (2020) [3] virtual perspective No CBD dynamics data are reported Ferrando et al (2021) [108] process identification No CBD dynamics data are reported Fortelli et al (2021) [109] process identification No CBD dynamics data are reported Lollino et al (2021) [110] process identification No CBD dynamics data are reported…”
Section: Appendix Amentioning
confidence: 99%